Argentina's new agreement with the IMF - Fernandes, Marcelo Pereira; Alves Junior, Antonio José; Jeronimo de Freitas, Alexandre; Christina Wegner, Rubia (Brazilian Keynesian Review, 2022)
The objective of this paper is to analyze Argentina's new agreement with the IMF. We will show that despite the country's fragile economic situation and an adverse external context, the Fernandéz government managed to conclude an agreement that brought some relief to Argentina, without the government committing to structural reforms that the Fund normally imposes.